The role of α-E-catenin in cerebral cortex development: radial glia specific effect on neuronal migration - Schmid, Marie-Theres; Weinandy, Franziska; Wilsch-Bräuninger, Michaela; Huttner, Wieland B.; Cappello, Silvia; Götz, Magdalena (Frontiers in Cellular Neuroscience, 2014)
During brain development, radial glial cells possess an apico-basal polarity and are coupled by adherens junctions to an F-actin belt. To elucidate the role of the actin, we conditionally deleted the key component α-E-catenin in the developing cerebral cortex. Deletion at early stages resulted in severe disruption of tissue polarity due to uncoupling of adherens junctions with the intracellular actin fibers leading to the formation of subcortical band heterotopia. Interestingly, this phenotype closely resembled the phenotype obtained by conditional RhoA deletion, both in regard to the macroscopic subcortical band heterotopia and the subcellular increase in G-actin/F-actin ratio. These data therefore together corroborate the role of the actin cytoskeleton and its anchoring to the adherens junctions for neuronal migration disorders.